THE INFLUENCE OF LEADERSHIP, WORK MOTIVATION, AND WORK ENVIRONMENT ON STAFF AND TEACHING PERFORMANCE IN SMP NEGERI 7 MENGWI - I Nyoman Andika Permana; I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Assets of the organization and have strategic roles within the organization, namely thinkers, planners, and control of organizational activities. Good performance is also apart from the cooperation between superiors and subordinates in establishing working relationships and often provides motivation to create a harmonious working atmosphere and besides that the leadership of superiors in a company organization is also one of the factors for the success of an organization . This study aims to analyze the influence of leadership, work motivation, and work environment on the performance of staff and teaching staff at SMP Negeri 7 Mengwi. This research was conducted at SMP Negeri 7 Mengwi with staff and teaching staff as respondents. The type of data used in this study is quantitative data. While the source uses primary data and secondary data. The number of samples taken is 32 respondents with saturated sampling method. This data is collected by means of questionnaires and documentation. These data were analyzed using multiple linear regression analysis assisted by the SPSS version 25 program. The results of this study indicate that the variable work motivation has a significant positive effect on employee performace and the work environment have a significant positive effect on employee performance. While the leadership variable has no positive effect on employee performance.